Analisis Efektivitas Administrasi Pembangunan dalam Mengelola Anggaran Daerah untuk Pembangunan Ekonomi Lokal - Satria Lam Syafi’i Simamora; Imsar Imsar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study employs a qualitative library research method with the primary objective of analyzing the effectiveness of development administration in the management of regional budgets to support local economic development. Development administration is a crucial component in the governance process, encompassing the planning, organizing, directing, and supervising of budget utilization to ensure that resources are allocated in a targeted, efficient, and sustainable manner. Within the context of local governments, the effectiveness of budget management is considered a key indicator of the success of regional development, as it directly reflects the ability of local authorities to implement policies that foster equitable and inclusive growth. The data for this study were obtained from various scientific literature sources, including academic journals, textbooks, and relevant government policy documents addressing budgeting and regional development. The findings of the analysis highlight that successful budget management is strongly influenced by bureaucratic capacity, particularly in terms of administrative competence, professional integrity, and institutional stability. Furthermore, transparency in budget planning processes plays a significant role in building public trust and preventing misallocation of resources. Equally important is the participation of the community in monitoring and evaluating budget implementation, which ensures accountability and responsiveness to public needs. In addition, synergy between legislative and executive bodies is identified as a determining factor in strengthening checks and balances, thereby enhancing the accountability of public fund management. The study concludes that effective development administration not only supports efficient allocation of financial resources but also contributes to accelerating local economic growth, reducing social inequality, and improving community welfare. Ultimately, this research is expected to provide valuable insights and serve as a reference for local governments in formulating strategies for more optimal, transparent, and participatory budget management practices